The greek and latin inscriptions in the governorate of ʿAjlun in north-west Jordan - Badr, Nabīl (2016)
ʿAjlun Governorate, the smallest in Jordan, is located in the north west of the Hashemite Kingdom of Jordan. It has already delivered some Greek inscriptions, but as in other parts of the country, new inscriptions appear from time to time. Some newly discovered inscriptions were separately reported in various articles. Due to their importance, an overview may be useful. Among them, an exceptional bilingual Neohellenic and Arabic inscription was found in the city of ʿAjlun. This text which commemorates the building of a church in the 19th cent. is here published for the first time.
Le gouvernorat de ʿAjlun, le plus petit de Jordanie, est situé au nord-ouest du Royaume Hachémite de Jordanie. Il a déjà livré quelques inscriptions grecques mais, comme dans d’autres parties du pays, de nouveaux documents apparaissent de temps en temps. Quelques inscriptions trouvées plus ou moins récemment ont été signalées ou ont été publiées séparément dans divers articles. En raison de leur importance, une présentation d’ensemble peut être utile. Parmi elles, une inscription bilingue exceptionnelle, néo-hellénique et arabe, a été trouvée dans la ville de ‘Ajlun. Ce texte qui commémore la construction d’une église au xixe s. est ici publié pour la première fois.
تقع محافظة عجلون، التي تُعد الأصغر في الأردن، شمالي غربي المملكة الأردنية الهاشمية .وقد سلّمَت سابقاً بضعة نقوش يونانية، لكن كما في الأقسام الأخرى من المملكة، تظهر من وقتٍ إلى أخَر وثائق جديدة. وُجدَت حديثاً بضعة نقوش تمّ الإشارة إليها أو نشرها بشكل منفصل في مقالات مختلفة. وبسبّب أهميتها، قد يكون من النافع عرض موجز لها. يوجد من بينها، نقشُ نادر بلُّغتَين، الهللينية الحديثة والعربية، عُثر عليه في مدينة عجلون. هذا النّص الذي يُخلّد ذكرى بناء الكنيسة في القرن التاسع عشر يُنشر هنا للمرّة الأولى
Keywords: épigraphie grecque; épigraphie latine; inscription bilingue néo-hellénique; inscription bilingue arabe; Greek epigraphy; Latin epigraphy; bilingual Neohellenic inscription; bilingual Arabic inscription; ʿAjloun; Jordanie; ʿAjlun; Jordan